Tinjauan Semiotik Terhadap Gambaran Dunia Menurut Kosmologi Hindu-Buddha, dan Batak - Ery Soedewo (Berkala Arkeologi Sangkhakala, 2007)
AbstractSimilarities in cosmology concept between Bataks tradition and Hindu-Buddhist tradition on three world existence is universal. But there’s a concept in Hindu-Buddhist that influenced on Batak’s cosmology concept.